2000
DOI: 10.1212/wnl.55.8.1158
|View full text |Cite
|
Sign up to set email alerts
|

Documented head injury in early adulthood and risk of Alzheimer’s disease and other dementias

Abstract: Moderate and severe head injuries in young men may be associated with increased risk of AD and other dementias in late life. However, the authors cannot exclude the possibility that other unmeasured factors may be influencing this association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
562
6
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 762 publications
(606 citation statements)
references
References 34 publications
21
562
6
3
Order By: Relevance
“…The most common form of AD is sporadic AD (SAD), accounting for more than 90% of all disease cases. While apolipoprotein E e4 allele is the best-documented genetic risk factor for SAD (Corder et al 1993;Saunders et al 1993;Strittmatter et al 1993), traumatic brain injury (TBI) represents the most robust environmental AD risk factor (Schofield et al 1997;Nemetz et al 1999;Plassman et al 2000;Jellinger et al 2001). TBI has been shown to induce an increase in cerebrospinal fluid (CSF) Ab levels (Raby et al 1998), as well as Ab deposition in the human brain (Nicoll et al 1995), and Ab plaques have been found within days after a single incident of TBI in humans (Roberts et al 1991;Graham et al 1995).…”
mentioning
confidence: 99%
“…The most common form of AD is sporadic AD (SAD), accounting for more than 90% of all disease cases. While apolipoprotein E e4 allele is the best-documented genetic risk factor for SAD (Corder et al 1993;Saunders et al 1993;Strittmatter et al 1993), traumatic brain injury (TBI) represents the most robust environmental AD risk factor (Schofield et al 1997;Nemetz et al 1999;Plassman et al 2000;Jellinger et al 2001). TBI has been shown to induce an increase in cerebrospinal fluid (CSF) Ab levels (Raby et al 1998), as well as Ab deposition in the human brain (Nicoll et al 1995), and Ab plaques have been found within days after a single incident of TBI in humans (Roberts et al 1991;Graham et al 1995).…”
mentioning
confidence: 99%
“…However, it is not clear whether these inflammatory "footprints" observed in the late stages of the pathogenesis of PD may merely be a reflection of reactive gliosis after the occurrence of the initial neuronal injuries. On the other hand, increasing evidence has suggested that early-life occurrence of inflammation in the brain, either as a result of exposure to infectious agents or brain injury, plays an important role in later-life development of PD (Ravenholt and Foege, 1982;Factor et al, 1988;Mattock et al, 1988;Williams et al, 1991;Casals et al, 1998;Plassman et al, 2000). The likelihood that inflammation plays a key role in the earlier stages of PD is significantly enhanced by the observation that the midbrain region is particularly rich in microglia (Lawson et al, 1990;Kim et al, 2000), which are readily activated by immunological challenges and neuronal injuries (Kreutzberg, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] What is less clear is whether mild TBI can also lead to cognitive impairment, with several studies showing negative results. [19][20][21] More than one million concussions occur annually in this country, with 300,000 resulting from sports-related activities.…”
Section: Discussionmentioning
confidence: 99%